Women's Empowerment In Msmes: Analysis Of Social And Economic Impacts - Dindin Abdurohim (CV Putra Publisher, 2023)
Empowering women in Micro, Small, and Medium Enterprises (MSMEs) plays a crucial role in achieving inclusive and sustainable economic development. This research focuses on analyzing the social and economic impacts of women's empowerment efforts in the MSME sector. Using of literature review, the study aims to illustrate the contributions of women's empowerment to economic development and social well-being. The research findings indicate that women's empowerment in MSMEs has positive economic impacts by increasing their participation in business activities. The implementation of training and mentoring programs has proven effective in enhancing women's managerial and entrepreneurial skills, contributing to increased family income. Socially, women's empowerment also creates positive effects by enhancing their roles in family decision-making and community involvement. Through a profound understanding of these impacts, this research provides a foundation for the development of more effective empowerment policies and programs. It involves various stakeholders to create an environment that supports the active role of women in MSMEs.